2018
DOI: 10.3233/jad-180166
|View full text |Cite
|
Sign up to set email alerts
|

Testing Hippocampal Memory in Prodromal Dementia with Lewy Bodies

Abstract: The Free and Cued Selective Reminding test (FCSRT) was used to assess memory in 19 patients with prodromal dementia with Lewy bodies (DLB) and 25 Alzheimer's disease (AD) patients. DLB scored better than AD in selective measures of the FCSRT: immediate total recall (p = 0.01) and index of sensitivity of cueing (p = 0.001), while free delayed and total memory scores were similarly impaired. The index of sensitivity of cueing held a sensitivity of 76% and specificity of 79% in distinguishing DLB. FCSRT could hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Donaghy et al 2018 2015only showed impairment in EF (g = −0.72; Stroop Colour test) and there were no significant differences in Jicha et al 2010after bias correction. MCI-LBs performed significantly better than MCI-AD on verbal memory outcome measures (immediate recall, delayed recall, and recognition) in three studies (Bussè et al, 2018;Cagnin et al, 2015;Yoon et al, 2015) with generally large ES (g = 0.66-3.80, mean g = 1.82).…”
Section: Mci-lb Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Donaghy et al 2018 2015only showed impairment in EF (g = −0.72; Stroop Colour test) and there were no significant differences in Jicha et al 2010after bias correction. MCI-LBs performed significantly better than MCI-AD on verbal memory outcome measures (immediate recall, delayed recall, and recognition) in three studies (Bussè et al, 2018;Cagnin et al, 2015;Yoon et al, 2015) with generally large ES (g = 0.66-3.80, mean g = 1.82).…”
Section: Mci-lb Resultsmentioning
confidence: 90%
“…Twenty-one variables showed poorer performance by MCI-LB relative to MCI-AD in visuospatial, attention, and psychomotor speed. Both Bussè et al (2018) and Cagnin et al (2015) reported poorer performance in MCI-LB in WM, visuospatial and visuoconstructive ability, and EF, with magnitudes ranging from medium (g = −0.56, Object Decision Visuospatial Test, Cagnin et al, 2015) to large (g = −0.95, Digit Span Backwards, Cagnin et al, 2015) and very large (g = −3.45, Pentagon Test number of angles, Busse, Hensel, Gühne, Angermeyer, & Riedel-Heller, 2006). Donaghy et al 2018 2015only showed impairment in EF (g = −0.72; Stroop Colour test) and there were no significant differences in Jicha et al 2010after bias correction.…”
Section: Mci-lb Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the individual contributions of encoding, consolidation, and retrieval mechanisms to the memory deficits of PD patients, we used the Free and Cued Selective Reminding Test (FCSRT; Buschke, Sliwinski, Kuslansky, & Lipton, 1997), a test widely used for the assessment of EM failure in mild cognitive impairment and dementia . This test has demonstrated high sensitivity and specificity to cognitive decline and dementia (Grober, Lipton, Hall, & Crystal, 2000), and is also a good tool to discriminate AD patients from other forms of dementia (Bussè et al, 2018;Lemos, Duro, Simões, & Santana, 2014;Teichmann et al, 2017). The FCSRT combined with the item-specific deficit approach (ISDA) introduced by Wright et al (2009) allows for the precise quantification of encoding, consolidation, and retrieval deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should thus consider sampling similar populations with balanced proportions of male and female participants. Second, our population was mainly defined on the basis of scores obtained in the FCSRT for which a low performance can be related to various neurodegenerative diseases associated to pathological aging such as AD, frontotemporal dementia or Lewy body disease ( Bertoux et al, 2014 ; Lemos et al, 2015 ; Bussè et al, 2018 ). For example, despite the very high sensitivity of FCSRT (e.g., 100% in Teichmann et al, 2017 ) for identifying typical AD patients, abnormal scores in FCSRT do not have an absolute specificity (e.g., 75% in Teichmann et al, 2017 ) for typical AD.…”
Section: Discussionmentioning
confidence: 99%